2022
DOI: 10.3390/curroncol29020071
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI in Patients with Testicular Tumors—Intra- and Interobserver Variability

Abstract: In general, magnetic resonance (MR) diffusion-weighted imaging (DWI) has shown potential in clinical settings. In testicles parenchyma, the DW imaging helps differentiate and characterize benign from malignant lesions. Placement and size of the region of interest (ROI) may affect the ADC value. Therefore, the aim of this study was to investigate the intra- and interobserver variability in testicular tumors when measuring ADC using various types of regions of interest (ROI). Two observers performed the ADC meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, our results suggest that the VOI 1 placement method likely improved the ability to differentiate between benign and malignant tumors. Our results are similar to those of Pederson et al, which studied a group of malignant testicular tumors consisting of 26 tumors and pointed out the highest value of whole-tumor VOI placement in diagnosing testicular tumors 9 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, our results suggest that the VOI 1 placement method likely improved the ability to differentiate between benign and malignant tumors. Our results are similar to those of Pederson et al, which studied a group of malignant testicular tumors consisting of 26 tumors and pointed out the highest value of whole-tumor VOI placement in diagnosing testicular tumors 9 .…”
Section: Discussionsupporting
confidence: 92%
“…HA analysis is a quantitative method for evaluating the statistical parameters in each image based on VOI placement to cover the entire tumor. Therefore, the histogram's shape and asymmetry reflect microstructural differences in tumor composition corresponding to histopathological grade, distinguishing benign and malignant tumors 8 , 9 . Previous studies have shown that placing the VOI so that it covers the entire tumor volume allows for a better assessment than the previous approach of placing an ROI on a specific slice or localized tumor region, often avoiding its cystic, necrotic, and hemorrhagic portions, leading to limitations in reflecting its heterogeneity, especially for malignant tumors that have more necrotic and bleeding portions than benign tumors 8 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All ROI methods (oval, freehand, small‐sample, and whole‐volume) showed excellent interobserver agreement, indicating that different ROI methods were objective and reliable for ADC measurements in fibrosarcoma. Previous studies have demonstrated good or excellent intraobserver or interobserver agreement for ADC measurements in hepatocellular carcinoma, 17 bladder cancer, 18 rectal cancer, 19 head and neck cancer, 20 testicular tumor, 21 and soft tissue masses 22 using different ROI methods, including the largest tumor slice, multiple small tumor samples, and whole tumor volume. Notably, the whole‐volume ROI method in the present study had the best reproducibility in ADC measurements, suggesting that the inclusion of the whole tumor volume method, which is not limited by the number and size of ROIs, leads to a decline in sampling errors and interobserver variability.…”
Section: Discussionmentioning
confidence: 99%